1996
DOI: 10.2134/agronj1996.00021962003600060007x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Involving Allelopathy in Cropping Systems

Abstract: Allelopathic inhibition typically results from the combined action of a group of allelochemicals which, collectively, interfere with several physiological processes. The objectives of this paper are to summarize research that illustrates the joint action of allelochemicals, and to provide evidence that both the amount and detrimental action of these compounds depends on the extent of associated abiotic and biotic stresses. Allelopathy is strongly coupled with other stresses of the crop environment, including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
175
2
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(207 citation statements)
references
References 49 publications
11
175
2
19
Order By: Relevance
“…Plantas liberam no ambiente diversos compostos do metabolismo secundário (Einhellig, 1996). Os efeitos observados pela utilização da semeadura em substituição, resultantes do convívio entre plântulas, provavelmente são devidos à liberação de compostos alelopáticos -alguns com maior e outros com menor atividade sobre espécies indicadoras.…”
Section: Resultsunclassified
“…Plantas liberam no ambiente diversos compostos do metabolismo secundário (Einhellig, 1996). Os efeitos observados pela utilização da semeadura em substituição, resultantes do convívio entre plântulas, provavelmente são devidos à liberação de compostos alelopáticos -alguns com maior e outros com menor atividade sobre espécies indicadoras.…”
Section: Resultsunclassified
“…In the leaf litter, however, the least content of oil [(2.36 ð 0.04) ml/100 g leaves] was determined and it was nearly half of that found in the juvenile or senescent leaves. Such variability in the content of essential oils (secondary metabolites) is not surprising as the amount of secondary metabolites changes with aging or metabolic state of the plant (Einhellig, 1996). Kong et al (2002) reported that the amount of volatile oils in Ageratum conyzoides increases under stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Esses agentes alelopáticos são geralmente compostos secundários produzidos pelas plantas e liberados por lixiviação, volatilização, decomposição e exudados da raiz (Inderjit & Dakshini 1992;1994). A produção de compostos secundários pode ser aumentada por diversos fatores ambientais como estresse hídrico, deficiência de nutrientes e temperatura (Einhellig 1996) situações comumentes encontradas no Cerrado.…”
Section: Introductionunclassified